(untitled) (Journal of Nobel Medical College, 2019)
Background: Maternal diabetes mellitus (DM) has been shown to be high risk factor for congenital anomalies. It carries 3-5 times higher risk of incidence compared to the general population. The aims of present study is to investigate and portray the incidence of congenital heart disease in infants of diabetic mothers and know the utility of echocardiography in the early diagnosis of CHD at Nobel Medical College teaching hospital, a tertiary care centre in the eastern part of Nepal and review the current literature. Material & Methods: This is a prospective observational study conducted in Nobel Medical College Teaching hospital, Kanchanbari, Biratnagar Nepal over the period of 12 months. A structured questionnaire was designed which included demographic profile and the Echocardiography findings. The collected data were analysed using window’s SPSS version 20. Results: In the present study of the total deliveries 1.99 % was diabetic mother comprising 208 deliveries.127 had undergone echocardiography in which 10.2 % (n=13) had anomalies. One hundred sixteen were term and 11 were preterm. PDA was the most common anomaly (38.4%) followed by VSD (23.1%) and HCM (15.4%). Conclusion: With the review of current literature it has been found that maternal diabetes mellitus is a significant risk factor for congenital heart disease so it is suggested that the presence of diabetes mellitus in a pregnancy should be taken as a strong suspicious of having CHD and infants should be screened for the same .so as to diagnose the anomaly at the earliest possible.